ANTIBIOTIC SUSCEPTIBILITY TEST OF PSEUDOMONAS AERUGINOSA AND STAPHYLOCOCCUS AUREUS WITH DISK DIFFUSION AND DILUTION METHOD - Raffi Joe Bhagaskara; Alyaa Shofura Ahmad; Syifa Regina Prasetyawan; Dewi Amelia; Deri Putra Pratama; Innayah Marda Hidayyah Tulloh; Naadhira Alya Putri; Indira Damayanti Putri; Alya Layyina Rabbani; Fathan Mubiin Ibnu Ismail; Jihan Tria Astuti; Naufal Brian Atmaja (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2023)
The susceptibility test is a test used to measure bacteria's sensitivity and vulnerability towards antibiotics. This study was to determine sensitivity of Pseudomonas aeruginosa and Staphylococcus aureus towards amoxicillin, neomycin, and sulfanilamide. In this study, the methods used in susceptibility tests are disk diffusion method and serial dilution. The disk diffusion method is a method with paper disks that already saturated the antibiotics, with one paper disk for each antibiotic, put the disk on the agar media that had been inoculated by the bacteria, then incubated and measured the inhibition zone. The dilution method was done by making a series of antibiotic dilutions in liquid media which added microbes inside. This test is to estimate the smallest concentration or Minimum Inhibitory Concentration (MIC) in the dilution series with no bacterial growth. The diffusion test shows no clear visible zone at all, so Pseudomonas aeruginosa and Staphylococcus aureus are resistant to amoxicillin, neomycin and sulfanilamide. The dilution test shows the clearest sample was on 0,25% concentrate, so amoxicillin's Minimum Inhibitory Concentration towards Staphylococcus aureus is 0,25%.